Shareholder Activism as A Mechanism Within Corporate Governance: A Theoretical and Empirical Review - Nyamita, Micah (The Journal of Accounting and Management, 2025)
Research on shareholder activism and corporate governance is considered inconclusive, both internationally and locally, due to ongoing debates, notably within firms. It is posited that shareholder activism should impact corporate governance. Numerous theories have been suggested to substantiate the inference, although there is no consensus among researchers regarding a particular theory that validates the theoretical claim. Consequently, the empirical evidence about the topic has remained inconsistent. The diversity in actual results has prompted numerous studies, primarily from diverse areas and types of organizations. This study conducted a theoretical and empirical evaluation of shareholder activism as a mechanism in corporate governance to emphasize the findings of previous research. A thorough literature analysis was conducted, analyzing 134 publications, from which results were derived from 86 papers by explaining the principal themes of this study. The analysis indicated that multiple theories have developed, with the predominant theory remaining the agency theory. The current empirical evidence is also inconclusive. Consequently, the evaluation substantiates the necessity for further research on the same themes across diverse geographies and various categories of organizations.